2013
DOI: 10.1111/ajgw.12049
|View full text |Cite
|
Sign up to set email alerts
|

Early defoliation in a temperate warm and semi-arid Tempranillo vineyard: vine performance and grape composition

Abstract: Background and Aims Early defoliation (ED) can reduce vine yield and improve fruit composition in vigorous vineyards. The objective of this study was to test the effectiveness of this technique for the Vitis vinifera (L.) cultivar Tempranillo under the temperate warm and semi‐arid climatic conditions of south‐eastern Spain. Methods and Results Four treatments were applied over three seasons to drip‐irrigated vines, planted with rows orientated north–south and shoots vertically positioned. Non‐defoliated vines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 29 publications
7
51
1
2
Order By: Relevance
“…15,16 Similar to TSS, the impact of leaf removal before or after flowering on TA is still controversial. Experiments carried out on 'Pinot noir', 'Trebbiano', 'Merlot' (V. vinifera L.), 'Cabernet Sauvignon', and 'Sangiovese' reported no impact of this technique on TA, 15,28,29 while an increase of TA was shown under leaf removal before flowering in 'Sangiovese' and in 'Tempranillo'.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Similar to TSS, the impact of leaf removal before or after flowering on TA is still controversial. Experiments carried out on 'Pinot noir', 'Trebbiano', 'Merlot' (V. vinifera L.), 'Cabernet Sauvignon', and 'Sangiovese' reported no impact of this technique on TA, 15,28,29 while an increase of TA was shown under leaf removal before flowering in 'Sangiovese' and in 'Tempranillo'.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, this results have not always been consistent between climates, vintages, and cultivars. 15,16 Despite the fact that this strategy has been suggested for high-yielding varieties, the reduction of crop size might help improve the composition of red grapes even in vineyards where leaf area-to-yield ratios are above limiting thresholds (0.8 m 2 /kg), 17 but crop size reduction via, for example, cluster thinning is normally applied by grape growers to improve grape composition. Indeed, there is a lack of information on how the reduction of crop size and the increase in leaf area-to-yield ratio can affect the accumulation of secondary metabolites and particularly volatiles such as methoxypyrazines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this sense, defoliation has been an important canopy management to improve the quantity and quality of the phenolic compounds of berries (Moreno et al, 2014), and the timing of leaf removal is another key factor in the accumulation of phenolic compounds (Gatti et al, 2012). In previous studies, Moreno et al (2014) also observed that leaf removal resulted in greater accumulation of phenolic compounds, whereas Tardaguila et al (2010) and Risco et al (2014) found that early leaf removal caused an increase in polyphenol content. It has been suggested that the biosynthesis of polyphenols is light dependent, favoring their accumulation (Sun et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Early leaf removal, associated with a high incidence of solar radiation, provides a reduction in total acidity contents, due to the degradation of malic acid Risco et al, 2014). This effect may also be a result of the direct exposure of clusters to the sun, which increases their temperature and, consequently, the rate of cellular respiration, causing malic acid degradation (Conde et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…At both harvests, leaf removal carried out until berries pepper-corn size phenological stages resulted wines with the lowest values of total acidity, while wines from plants without leaf removal show the highest total titratable acidity. Early leaf removal associated with high solar radiation provides a reduction in berries acidity due to the greater degradation of malic acid [24,25]. For pH of the wine, it was observed that earlier leaf removal, before véraison, showed elevation of pH ( Table 1).…”
Section: Resultsmentioning
confidence: 99%